A Mobile Augmented Reality Application for Automotive Sparepart Installation - Arifitama, Budi; Abdillah, Zihan Noor; Syahputra, Ade; Permana, Silvester Dian Handy; Yaddarabullah, - (SOTVI, 2022)
Automotive exterior spare parts retailers frequently sell exterior spare parts for a range of cars via direct sales transactions and online media. A major issue has come up for consumers who purchase products online must install spare parts independently, with limited instructions that make it difficult for customers to install the replacement components. This is demonstrated by nearly 50% of online consumers complaining to the seller about installation errors, indicating the need for a solution to these issues. Augmented reality was used as a solution to educate how to install automotive exterior spare parts. In this work, the Spatial Tracking technology is utilized to project objects from a viewpoint in order to send data digitally and show the 3D model to the object's surrounds in real time.Â This study included as samples rear-view mirrors, headlights, stop lamps, and fog lamps. According to the study's findings, The user acceptance test was carried out by online consumers who buy spare parts at the store, and the results of the average percentage score of the entire questionnaire by more than 53% agree and strongly agree that the use of augmented reality can ease the spare-part installation bought online, the results of testing the AVAR application by the user are successful and well accepted.